EFFECT OF DRYING TEMPERATURE AND TIME ON TABLET FORMULATION OF MORINGA LEAF (Moringa oleifera) EXTRACT WITH WET GRANULATION METHOD USING FLUID BED DRYER - Isnawati, Nafisah; Zulfatul Maskuriah, Dian; Wicaksono, Yudi (International Journal of Islamic and Complementary Medicine, 2021)
Moringa leave is medicinal plant type that often used by society. Flavonoid and saponin are the content of moringa leave which have benefit as immunomodulator. Moringa leave using can be more practical and easy to used by making as pharmaceutical preparation. Drying temperature and time have a great effect on the physical properties of granule and tablet manufacturing. The objective of this research is to find out the effect of drying temperature and time on the physical-mechanical properties of granule and physical-disintegrant properties of moringa leave extract tablet by wet granulation method. The research method using experimental laboratory methods is correlational (causation). Moringa leave extract tablet was made with 6 formulations by various drying temperature and time. Drying temperature and time which used are FI 40°35', FII 50°35', FIII 60°35', FIV 40°45', FV 50°45', FVI 60°45'. Each formulation was carried out physical properties test of granule and tablet. The data obtained were compared to the pharmacopoeai and other literature and carried out statistical test. In order to know the effect of temperature using Shapiro-Wilk test, then continued ANOVA test, while for the effect of time using independent sample T-test with 95% confidence level, then continued Turkey-HSD test. The result of the test showed that the differences of drying temperature and time have effect on the physical properties of tablet, namely, hardness, brittleness, and disintegration time. The increasing of drying temperature and time are able to reduce the brittleness, increase the hardness, and prolong disintegration time of tablet.